(untitled) (Semiárida, 2024)
The objective of this study is to examine changes in atmospheric water demand in the central semi-arid Pampas region over the last 30 years through evaporation and reference evapotranspiration (ETo). Data were obtained from the agrometeorological station of the College of Agronomy at UNLPam located in Santa Rosa, La Pampa. Evaporation was measured using an American-type A pan (E-T), and ETo was estimated using the Penman-Monteith equation (ETo-PM) for the period 1988-2019. Results showed that annual E-T ranged from 1850.0 to 2940.0 mm, while annual ETo-PM varied from 1130.0 to 1620.0 mm. The average annual E-T was 2332.7 mm ± 320.8 mm, and the average annual ETo-PM was 1346.4 mm ± 145.8 mm. Despite differences in absolute values, E-T and ETo-PM were directly associated (p<0.01), consistent with previous studies in other parts of the world. The annual tank coefficient (kt), defined as the slope of the regression line between ET and ETo, was 0.5713. According to this kt, annual E-T overestimated ETo-PM by 75 %. Seasonally (spring, summer, autumn, and winter), ET overestimated ETo between 66 % and 100 %. Both annual E-T and ETo showed an increasing trend (p<0.05). Considering that E-T is a direct measurement and ETo-PM is an estimation, and given the substantial differences in absolute values, there is a need for a lysimeter to precisely measure atmospheric and crop water demand.